The Specific Herbs Used As Antidotes In Nanju Murivu Nool-A Single Book Review - Thayalini, T.; Rakulini, R.; Janshe, S. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2017)
Nanjiyal (Toxicology) is one of the division of Siddha Medicine. The Antidotes against different kinds of poisons is found vastly dispersed in siddha texts. Herbs, Minerals and Metals, animal materials are used in the preparation of siddha drugs from ancient period. Many herbs are used as an antidote in different form of drug in the treatment of Thaathu nanju (Minerals and metals) and thavarananju (Plant poisons). Previous report on Siddha antidotes against Plant poison and minerals and metal poison has not been published. The aim of the study is to identify the herbs which are mentioned as antidotes in Nanju Murivu Nool. This book was obtained from the library of Unit of Siddha Medicine. Ninety seven (97) compound drugs were identified as antidotes for treating poison of metals and minerals and plants. Out of 97, 94(97%) are internal medicine. Among the 94 medicines, 32(34%) are Kudineer, 25(27%) katkam and 13(14%) Juice, 5(5%) ghee and 4(4%) Paspam. 74 herbs were identified from the 94 internal medicine. Among the 74, 38 (51%) herbs used in the treatment of minerals and metals poisoning and 36(49%) herbs used for treatment of plant poisoning. Different parts were identified from the 74 herbs. They are Leaves (11), root (8), Bark (4) root bark (3), Yam (3) for herbal poisoning. Root (9), root bark (8), leaves (6), bark (4) as antidotes in the treatment of minerals and metals poisoning. Among the parts mentioned as antidotes, 6 families were identified. They are fabaceae, cucurbitaceae, laminaceae, solanaceae, malvaceae & laminaceae. 4 plants were identified from the family Fabaceae. They are Indigofera tinctoria (root bark), Cassia auriculata (leaf), Sesbania grandiflora (leaf) and Pongamia pinnata (root bark). Decoction is identified as antidotes in high percentage. Leaves are used as an antidote in the treatment of herbal poisoning at the same time root and root bark are used in the treatment of mineral and metal poisoning as antidotes.
Keywords: Herbs; Antidotes; Book review